Environmental effects of densely planted willow and poplar in a silvopastoral system : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (Ph. D.) in Agroforestry, Institute of Natural Resources, Massey University, Palmerston North, New Zealand - Hussain, Zaker (Massey University, 2007)
New Zealand, having large areas of hilly landscapes, is subject to the risk of soil erosion, and summer and autumn droughts that limit pasture growth, which in turn affects the livestock-based economy. The nitrogen and phosphorus input in fertilisers coupled with livestock excreta and soil disturbance impose a serious threat to downstream water quality. The planting of trees is one option used to decrease soil erosion, increase the quantity of forage and manage runoff. To date, research has mainly focused on wide spaced poplar trees for feed quality and their effects on understorey pasture growth. However, there is increasing interest in the use of densely planted willow and poplar for fodder purpose. The effects of young (< 5 yrs old) willow and poplar planted at close spacing on runoff, soil erosion, growth of understory pasture and nutrient losses have never been studied in New Zealand. Three field trials (two at Crop and Research Unit, Moginie, Manawatu and one at Riverside Farm, Masterton) were conducted between October 2004 and November 2006 that incorporated comparative establishment and growth of densely planted willow and poplar and their effects on soil moisture, runoff, sediment load and nutrient losses from grazed and fertilised farmland. It was concluded that densely planted willow and poplar (3-4 yrs) reduced total nitrogen (TN) and dissolved reactive phosphorus (DRP) by 47 % each and sediment load by 52 %. Young trees reduced surface runoff and soil moisture more as they aged. However, due to their deciduous nature willow and poplar were not effective in reducing surface runoff in winter and early spring. Sheep preferred camping under trees, especially in late spring and summer, and this led to greater deposition of dung and urine under trees than open pasture. Sheep grazing, especially in winter, significantly increased sediment and nutrient loads in runoff water. The N and P fertiliser application increased nutrient load in runoff water well above the threshold level required to initiate algal growth to create eutrophication. Densely planted willow and poplar significantly reduced understorey pasture growth by 23 % and 9 %, respectively, in their second year at Moginie, mainly due to shade, but coupled with soil moisture deficit in summer. The pasture growth in a willow browse block was 52 % of that in open pasture as a result of shade and differences in pasture species composition. Sheep browsing reduced willow leaf area significantly. Willow and poplar survival rates were similar (P > 0.05) after two years of establishment (100 % vs 90.5 %, respectively). However, willow grew faster than poplar in height (1.90 vs 1.35 m), stem diameter (43.5 vs 32.6 mm), canopy diameter (69 vs 34 cm) and number of shoots (8.7 vs 2.3) at the age of two years, respectively. The research clearly demonstrated that densely planted young willow and poplar trees can reduce runoff, sediment load and nutrient losses from farmland to freshwater, but shade and soil moisture can limit pasture growth under trees. It is recommended that willow and poplar should be planted at wide spacing on the whole farm to minimise loss of pasture. Where blocks of trees are necessary, such as willow browse blocks, sheep browsing can be used as a tool to reduce shade to improve pasture growth. Livestock access to riparian strips should be minimal to avoid livestock camping that can have deleterious effects on water quality.
Keywords: Agroforestry; Poplar; Willow; Fodder trees; Soil conservation; Hill farming; New Zealand; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300600 Forestry Sciences::300606 Agroforestry